(untitled) (International Journal of Innovative Computing, 2014)
PobMC is an adaptive scalable approach whichuses policies to control and adapt the system behaviour.Moreover, PobMC has the capability to decouple the adaptationconcerns from the application code. Since policies are used togovern the system behavior, conflicts may arise in the set ofpolicies and also may arise during the refinement process,between the high-level goals and the implementable policies.Furthermore, policy conflict may result from propagation,action composition and other constraint policies, which cannotbe detected by simply comparing authorization policies. In thispaper we classify our system policy conflicts to verify thatpolicies enforced correctly. Then, we present a static analysis toaddress the overlap of domains when there are two or morepolicies are enforced simultaneously. In addition, the paperprovides temporal specification patterns to detect each type ofconflicts. The evaluation result shows that the performance ofPobMC is better than the previous works. Less than a second isenough to perform every task as individual.